2012
DOI: 10.1007/s13594-012-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of HS-SPME–GC-MS-derived variables for monitoring ripening-induced changes in cheese volatile compounds

Abstract: Headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and multivariate statistical analysis (MVA) are widely employed in the analyses/comparison of cheese volatiles. One shortcoming of this approach is that the SPME fiber-coat polarity has a significant effect on the adsorption of volatiles and thus, on the results of MVA. The aim of this study was to test the applicability of different sets of MVA variables, obtained from HS-SPME-GC-MS experiments using the non-polar polyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Fiber coated with PDMS was better in recognizing the contribution/concentration of single dominant volatile compounds in the previous experiment (Milosavljević et al, 2012). Before using for the extraction of the samples studied, the fiber was preconditioned according to the instruction in the GC injection port at 260℃ for 20 min.…”
Section: Off-flavors Removal Two Different Methods Embedding Andmentioning
confidence: 99%
“…Fiber coated with PDMS was better in recognizing the contribution/concentration of single dominant volatile compounds in the previous experiment (Milosavljević et al, 2012). Before using for the extraction of the samples studied, the fiber was preconditioned according to the instruction in the GC injection port at 260℃ for 20 min.…”
Section: Off-flavors Removal Two Different Methods Embedding Andmentioning
confidence: 99%
“…In this study, HS-GC revealed the presence of all VOC groups in Swiss-Dutch-type cheeses. The presence of alcohols, esters, ketones, short-chain and medium-chain fatty acids was also determined in Serbian Pirotski kačkavalj cheese [Milosavljević et al, 2012] and French Cantal cheese [De Freitas et al, 2007]. According to Pastink et al [2008], considerable differences in the fl avor-forming ability of LAB exist not only between species, but also between strains.…”
Section: The Voc Content Of Swiss-dutch-type Cheesementioning
confidence: 99%
“…Advanced computational methods, such as HCA, PCA or partial least squares (PLS) regression, are increasingly often used in studies of this type. Milosavljević et al [2012] relied on AHC and PCA to compare contents of VOC determined by different gas chromatography methods. Based on an analysis of GC data, they concluded that the results of AHC and PCA should be analyzed in combination to produce a more comprehensive VOC profi le of ripened cheeses.…”
Section: Statistical Analysis Of Voc Profi Lesmentioning
confidence: 99%